Perancangan UI/UX Website Bandung Bawah Tanah Yang Responsif - Darsiti Darsiti; Novita Anggraini; Mamok Andri Senubekti; Adinda Salsabila (Jurnal Manajemen Informatika & Teknologi, 2025)
This research is entitled “Responsive Bandung Bawah Tanah Website UI/UX Design”. Bandung Bawah Tanah is a website created to meet the needs of building cultural narratives about the independent music scene in Bandung and Indonesia, to become a bridge between the music community and the academic realm, technically this website is used as an information and communication channel for music activists to jointly conduct research, writing, and building narratives about the underground music scene. The research objective intends to create a UI/UX design design model using the Human Centerd Design (HCD) approach. Using this HCD approach will ensure that this website is not only informative, but also provides an optimal user experience, so that it can be easily accessed by various groups, especially the younger generation who are the main targets.